2015
DOI: 10.1159/000439064
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Circulation Predicts the Size of the Infarct Core and the Proportion of Salvageable Penumbra in Hyperacute Ischemic Stroke Patients Treated with Intravenous Thrombolysis

Abstract: Background: We studied the impact of collateral circulation on CT perfusion (CTP) parametric maps and the amount of salvaged brain tissue, the imaging and clinical outcome at 24 h and at 3 months in a retrospective acute (<3 h) stroke cohort (105 patients) with anterior circulation thrombus treated with intravenous thrombolysis. Methods: Baseline clinical and imaging information were collected and groups with different collateral scores (CS) were compared. Binary logistic regression analyses using good CS (CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
5
22
0
1
Order By: Relevance
“…This may be due to frequent use of extracranial stenting in the CASOD population (70%) as well as the fact that chronically ischaemic tissues have a greater tendency for reperfusion injury. Moreover, our study confirms historical data, showing that patients with poor collaterals have lower ASPECTS, larger CTP core at baseline, lower rates of successful reperfusion, worse functional outcomes and larger FIVs .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be due to frequent use of extracranial stenting in the CASOD population (70%) as well as the fact that chronically ischaemic tissues have a greater tendency for reperfusion injury. Moreover, our study confirms historical data, showing that patients with poor collaterals have lower ASPECTS, larger CTP core at baseline, lower rates of successful reperfusion, worse functional outcomes and larger FIVs .…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, other studies of unique features and determinants of stroke mechanism (cardioembolic versus atherosclerotic) failed to demonstrate an association between stroke etiology and collateral flow [25,26]. Similarly, two recently published small series evaluated the impact of collaterals on clinical and imaging outcomes in LVOS [3,17]. While they confirmed good collaterals were associated with favorable outcomes, both failed to demonstrate that stroke etiology was a predictor of collateral status.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral status, beyond age, diabetes, NIHSS onset, ASPECTS, and recanalization, can be used to determine infarction and ischemic penumbra volumes (Rusanen, Saarinen, & Sillanpaa, ) and was demonstrated to be positively associated with favorable functional outcomes in both the MR CLEAN trial (Berkhemer et al, ) and the ESCAPE trial (Goyal et al, ). Furthermore, after correcting for stroke severity, Agarwal found that good collateral status was the only independent predictor of improvement in clinical status (Agarwal, Bivard, Warburton, Parsons, & Levi, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ASPECTS value has been shown to be associated with vascular pathology [21,22] and is a simple and accurate predictor of functional outcome after thrombolytic treatment [20,23,24]. Patients with an ASPECTS value higher than 7 will probably respond to treatment, whereas those with a value lower than 5 are much less likely to benefit [25].…”
Section: Introductionmentioning
confidence: 99%